Objectification and belittling of Sibyl Vane in Oscar Wilde’s Novel The Picture of Dorian Gray - Khan, Inam Ullah; Hassan, Syed Sabih Ul; Imran, Said (Pakistan Languages and Humanities Review, 2023)
The purpose of the study is to locate elements of feminism in Oscar Wild’s novel ‘The Picture of Dorian Gray’. It is argued that the male characters are the main focus of the story, while the female characters are treated as supporting characters. Through their gaze and words, the male characters objectify and denigrate the female characters. Females are regarded as nothing more than pretty faces for pleasure-seeking. Elements of objectification are highlighted in the novel by employing the theory of objectification. An in-depth examination of the novel through the lens of objectification theory reveals the shocking reality of male characters treating female characters, particularly Sibyl Vane, as objects. It is concluded that men in the novel treat women brutally. They are either regarded as fools or empty pots. They are treated as something that can be bought, sold, and replaced rather than as a human being with autonomy and subjectivity. Furthermore, other studies could be conducted on the same while applying different linguistic approaches such as pragmatics, critical discourse analysis (CDA) etc.